Research of multisensor characteristics based on optical fiber - A. O. Zenevich; S. V. Zhdanovich; H. V. Vasilevski; A. A. Lagutik; T. G. Kovalenko; T. M. Lukashik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The research results of multisensors based on optical fiber, the principle of which is to change the conditions of propagation of optical radiation in the optical fiber in the places where macro-bends are formed at the points of impact, are presented in the paper. The formation of macro-bends leads to an additional attenuation of the power of optical radiation propagating through the optical fiber. A single-mode optical fiber was used with the parameters, which are supported by numerous manufacturers and comply with the recommendations of ITU-T G.655. The measurements were carried out for four wavelengths of optical radiation (1310, 1490, 1550, 1625 nm), corresponding to the transparency windows of the optical loss spectrum of the optical fiber. Using optical reflectometry methods, it was determined that the amount of attenuation of optical radiation of each macro-bend formed at the point of action of the multisensor does not depend on the number of simultaneously formed macro-bends and also does not depend on the location of the point of action along the length of the multisensor. The dependences of the attenuation of the optical radiation power introduced by the macro-bends of the optical fiber on the radius, length, or angle of the macro-bends formed at the multisensory impact points are determined experimentally. The obtained dependences also allow one to determine the optimal parameters of the formed macro-bends of the multisensor to obtain the maximum range of attenuation change for each value of the wavelength. The values of the minimum distance between the impact points, the maximum number of impact points and the optimal values of the radius and angle of the optical fiber macro-bend at the impact points are determined. The results obtained provide opportunities to continue the development of multisensors that allow us to receive information about parameters from several impact points, that are located on a single optical fiber, simultaneously.